New approaches to science and technology cooperation and capacity building (UN New YorkUS, 1998)
Deals with analytical and conceptual aspects of the framework in which technology cooperation takes place. Describes and analyses the experience of various cases of technology cooperation at the national, regional and sectoral levels as well as general cases of capacity-building in human resources. Concentrates on various policy aspects of science and technology development and cooperation and endeavours to formulate policy elements related to resources development in general.
DC